2016
DOI: 10.1371/journal.pone.0154119
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Insulin Resistance and Absence of Inflammation Characterize Insulin-Resistant Grade I Obese Women

Abstract: ContextObesity is associated with insulin-resistance (IR), the key feature of type 2 diabetes. Although chronic low-grade inflammation has been identified as a central effector of IR development, it has never been investigated simultaneously at systemic level and locally in skeletal muscle and adipose tissue in obese humans characterized for their insulin sensitivity.ObjectivesWe compared metabolic parameters and inflammation at systemic and tissue levels in normal-weight and obese subjects with different insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 91 publications
0
31
1
Order By: Relevance
“…Furthermore, BMI was associated with CRP in FM. This implies a peripheral low-grade inflammation and could potentially contribute to reduced muscular IGF-1 response in overweight women with FM [35–37]. However, in the present study, BMI did not correlate with the acute IGF-1 response.…”
Section: Discussioncontrasting
confidence: 69%
“…Furthermore, BMI was associated with CRP in FM. This implies a peripheral low-grade inflammation and could potentially contribute to reduced muscular IGF-1 response in overweight women with FM [35–37]. However, in the present study, BMI did not correlate with the acute IGF-1 response.…”
Section: Discussioncontrasting
confidence: 69%
“…A muscle defect in the activation of the insulin meta bolic pathway (Akt phosphorylation) was identified as an early mechanism of insulin resistance development in these populations (Amouzou et al 2016). Along with the study by Amouzou et al, recent animal data has also suggested the existence of alternative mechanisms, independent of previously proposed skeletal muscle inflammation, to generate insulin resistance (Evers-van Gogh et al 2016; Rivas et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on humans are limited and reports are inconsistent. While some authors report an association between obesity and increased infiltration of skeletal muscle macrophages (Torres et al 2004; Varma et al 2009), others report little evidence of macrophage accumulation in skeletal muscle in obesity with or without type 2 diabetes (Xu et al 2003; Tam et al 2012; Amouzou et al 2016). Consequently, we conducted the present study in obese and lean humans with the goal of further clarifying if obese skeletal muscle becomes infiltrated with macrophages as it happens with obese adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Amouzou et al (2016) report leptin increased from 14.7 ng/ml in nonobese controls to 44.6 and 44.7 ng/ml, respectively, in insulinsensitive and insulin-resistant obese postmenopausal women, 370 aged between 50 and 64-years old [97]. Interestingly, males appear to be more sensitive to the effects of leptin, and therefore exhibit lower concentrations compared with females; with leptin concentration and leptin receptor inversely correlated with serum testosterone [98].…”
Section: Adipocytokines: Leptin and Adiponectinmentioning
confidence: 93%
“…Adiponectin promotes glucose utilization and fatty acid oxidation, and reduction of this adipocytokine is associated with insulin resistance [101]. For example, Amouzou et al (2016) 385 reported a decrease in adiponectin from 17.4 ng/ml in nonobese controls to 12.1 and 9.3 ng/ml in insulin-sensitive and insulin-resistant obese postmenopausal women, respectively [97]. Kim et al (2015) suggest the inhibition of adiponectin amongst the obese may be due to, obesity-induced 390 proinflammatory cytokines inducing the hypermethylation of compact chromatin structures in the adiponectin gene promoter by the methyl transfer enzyme DNA methyltransferase 1 (DNMT1), impeding the expression of adiponectin [102].…”
Section: Adipocytokines: Leptin and Adiponectinmentioning
confidence: 99%